2006
DOI: 10.1063/1.2158714
|View full text |Cite
|
Sign up to set email alerts
|

Simulation Results Related to Stochastic Electrodynamics

Abstract: Abstract. Stochastic electrodynamics (SED) is a classical theory of nature advanced signi…cantly in the 1960s by Trevor Marshall and Timothy Boyer. Since then, SED has continued to be investigated by a very small group of physicists. Early investigations seemed promising, as SED was shown to agree with quantum mechanics (QM) and quantum electrodynamics (QED) for a few linear systems. In particular, agreement was found for the simple harmonic electric dipole oscillator, physical systems composed of such oscilla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 81 publications
2
13
0
Order By: Relevance
“…The simulations of Cole and Zou typically ran for about 10 −11 sec or roughly 100, 000 orbits and showed that as time increased, the radial distribution in r tended to look more like that predicted by quantum mechanics. In subsequent simulations using 30 PCs, Cole increased the span of wavelengths used for the applied zero-point field from 10 4 to 10 6 and found ionization occurred unless they increased the precision of the computation [8]. These preliminary results were only for about 10 −12 sec, about one tenth the time of the previous work and showed general agreement with the previous work.…”
Section: Sed Simulations Of the Ground State Of The H Atomsupporting
confidence: 72%
See 1 more Smart Citation
“…The simulations of Cole and Zou typically ran for about 10 −11 sec or roughly 100, 000 orbits and showed that as time increased, the radial distribution in r tended to look more like that predicted by quantum mechanics. In subsequent simulations using 30 PCs, Cole increased the span of wavelengths used for the applied zero-point field from 10 4 to 10 6 and found ionization occurred unless they increased the precision of the computation [8]. These preliminary results were only for about 10 −12 sec, about one tenth the time of the previous work and showed general agreement with the previous work.…”
Section: Sed Simulations Of the Ground State Of The H Atomsupporting
confidence: 72%
“…Cole and Zou performed the first simulations of the hydrogen atom [3] [8]. They retained the effect of the magnetic field, approximated the radiative term as discussed above, and did not use a dipole approximation.…”
Section: Sed Simulations Of the Ground State Of The H Atommentioning
confidence: 99%
“…Speculatively, but quite possibly, the source of these difficulties lies in accurately dealing with the nonlinear stochastic differential equations in SED for these problems. However, even if this can be satisfied, it is most likely there will still be differences that should clearly be testable by experimental means (Cole, 2005).…”
Section: Origin Of Zero-point Field Energymentioning
confidence: 99%
“…According to the quantum vacuum inertia hypothesis (Haisch et al, 1994;Rueda and Haisch, 1998a;1998b;2005), as well as the connectivity approach of Nickisch and Mollere (2002), at least some component of inertial mass derives from charge interactions with the ZPF. It is possible to investigate the electromagnetic basis of inertial mass experimentally by using Casimir plates immersed in a plasma.…”
Section: Electron Inertial Mass Testmentioning
confidence: 99%
“…In 1907 in a letter to Einstein, he said: "I am not seeking the meaning of the quantum of action (light quantum) in the vacuum but rather in places where emission and absorption occur, and I assume that what happens in the vacuum is rigorously described by Maxwell's equations," see, for example, [222]. We also mention stochastic electrodynamics (SED) -a variant of classical electrodynamics which postulates the existence of a classical Lorentz-invariant radiation field (zero point field, Marshall and Brafford, Boyer, de la Pena and Cetto, Coli see, e.g., [41], [53]- [57], [46], see also [42], [224]). The presence of this field plays the crucial role in SED's description of quantum effects.…”
Section: Now We Discuss the Notion Of Photon It Is Well Known That Amentioning
confidence: 99%